Intervening at Home and Then at School : A Randomized Evaluation of Two Approaches to Improve Early Educational Outcomes in Tonga - Macdonald, Kevin (World Bank, Washington, DC, 2018)
This paper evaluates and compares two randomized interventions in Tonga, one targeting the home environment of children up to age 5 and one targeting the school environment for first and second grade students. The first intervention supports communities to set up and run playgroups that aim to improve caregiver-child interaction at home and ultimately improve children's readiness for school. Among children of mothers without high school education, being in a treatment community positively affects the school readiness literacy domains and overall score by 0.19 and 0.2 standard deviation, respectively, for girls and the literacy domains for boys by 0.17 standard deviation. The second intervention provides teachers with training, materials, and coaching to improve reading instruction practices and students’ reading ability. It increased average early grade reading scores by approximately 0.18 standard deviation per year of exposure. Two cohorts of children were potentially exposed to both interventions, providing an opportunity to compare, for the same population of children, the effects of an early childhood intervention with a school-based intervention using a common measure of learning achievement. The school readiness intervention is found to have positive effects on early grade reading scores only among children in the reading intervention’s control group; effect sizes of approximately 0.29 standard deviation were found at the end of second grade for children exposed to one year of the school readiness intervention and at the end of first grade for girls exposed to two years of the intervention.